Polyelectrolyte pH-Responsive Protein-Containing Nanoparticles: The Physicochemical Supramolecular Approach - Riabtseva, Anna; Kaberov, Leonid I; Kučka, Jan; Bogomolova, Anna; Stepanek, Petr; Filippov, Sergey K; Hruby, Martin (Langmuir, 2017)
We report on the physicochemical properties and self-assembly behavior of novel efficient pH-sensitive nanocontainers based on the Food and Drug Administration-approved anionic polymer Eudragit L100-55 (poly(methacrylic acid-co-ethyl acrylate) 1:1) and nonionic surfactant Brij98. The features of the interaction between Eudragit L100-55 and Brij98 at different pH values and their optimal ratio for nanoparticle formation were studied using isothermal titration calorimetry. The influence of the polymer-to-surfactant ratio on the size and structure of particles was studied at different pH values using dynamic light scattering and small-angle X-ray scattering methods. It was shown that stable nanoparticles are formed at acidic pH at polymer-to-surfactant molar ratios from 1:43 to 1:139. Trypsin was successfully encapsulated into Eudragit-Brij98 nanoparticles as a model bioactive component. The loading efficiency was determined by labeling trypsin with radioactive iodine-125. Eudragit-Brij98 nanoparticles effectively protected trypsin against pepsin digestion. The results showed that trypsin encapsulated into novel pH-sensitive nanocontainers retained more than 50% of its activity after treatment with pepsin compared with nonencapsulated trypsin. The described concept will contribute both to understanding the principles of and designing next-generation nanocontainers.
Keywords: Cattle; Animals; skot; velikost částic; trypsin; polyelektrolyty; Scattering, Small Angle; Hydrogen-Ion Concentration; Surface-Active Agents; Particle Size; Nanoparticles; Polyethylene Glycols; Drug Carriers; dynamický rozptyl světla; Plant Oils; maloúhlový rozptyl; Acrylic Resins; akrylové pryskyřice; nanočástice; polyethylenglykoly; X-Ray Diffraction; difrakce rentgenového záření; oleje rostlin; nosiče léků; Polyelectrolytes; povrchově aktivní látky; Trypsin; zvířata; Dynamic Light Scattering; koncentrace vodíkových iontů; Iodine Radioisotopes; radioizotopy jodu